Constructive (Fa'alan) and (Fa’el) in the basmalah A study in both linguistic and interpretive directions - , م. سلام حسون ناصر (Thi Qar Arts Journal, 2021)
This research is a scientific attempt to read what our scholars, both ancient and modern, have provided us with, as the basmalah occupied an appropriate space in their exegetical works, or those concerned with the sciences of the Qur’an, in addition to the linguistic ones.The research was based mainly on looking at the two structures (Al-Rahman and Al-Rahim) and what was said about them: from the two sides of the structure, and the meaning.The research was divided into two sections: the first topic dealt with the study of these two structures from the linguistic direction, with its (ascending) levels, starting from the phonemic level, then the morphological, then the lexical, and ending with the grammar, in which the views of linguists and commentators were presented from this perspective, and the different opinions reported on the two levels of the structure. , meaning.As for the second topic, it studied the two constructors from the interpretive direction, so the statements of the commentators - ancient and modern - revealed the intention of their indications, as they showed many aspects in the possible meanings of presenting (Al rahaemya) over (Al rahman), and the indication of the initiation of the two structures of mercy in the beginning of the Holy Qur’an.The approach followed in the research was a descriptive and analytical approach, as we start with the purpose of the phenomenon, and explain its horizons - Al-Maqali and Al-Maqami - and then analyze that in an analysis that contributes to highlighting the intended meanings of their expression.The research has adopted a large group of old and modern works, and it has expanded; The study broadened the horizons, as it included works: phonetic, morphological, grammatical, lexicon, and interpretations of the Noble Qur’an from various fields: linguistic, historical, jurisprudential, and mystical, as well as some recent studies.The research showed useful results in the Quranic lesson, on two levels: its language, and its interpretation.